2016
DOI: 10.4028/www.scientific.net/msf.858.639
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Investigation of 4H-SiC Trench Properties Dependence on Channel Concentration, Crystallographic Plane, and MOS Interface Treatment

Abstract: We have systematically investigated the trench properties of 4H-SiC for p-type channel doping level formed by epitaxial growth, crystallographic plane, and MOS interface treatment. Our results show that the channel mobilities on the (1-100), (11-20), (-1100), and (-1-120) planes gradually decreased in the range from 1 × 1016 to 1 × 1017 cm-3 as the epitaxial channel concentration increased. An inevitable tradeoff existed between channel mobility (field-effect mobility, µFE) and threshold voltage (Vth) in trenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Mobility depends on both the doping concentration of the p-epitaxial layer and the process of fabricating the trench gate. 11,12,30) The mobilities in the TCAD were therefore adjusted on the basis of the experimental results by simply setting the parameters that influenced the normal electric field effect on the mobility, 35) because there was no information of the surface state density at the SiO 2 =SiC interface of the trench gate. R ON A of less than 3 mΩ cm 2 at a drain current density of 400 A cm −2 was obtained at the p-epitaxial doping concentration below 2 × 10 17 cm −3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobility depends on both the doping concentration of the p-epitaxial layer and the process of fabricating the trench gate. 11,12,30) The mobilities in the TCAD were therefore adjusted on the basis of the experimental results by simply setting the parameters that influenced the normal electric field effect on the mobility, 35) because there was no information of the surface state density at the SiO 2 =SiC interface of the trench gate. R ON A of less than 3 mΩ cm 2 at a drain current density of 400 A cm −2 was obtained at the p-epitaxial doping concentration below 2 × 10 17 cm −3 .…”
Section: Resultsmentioning
confidence: 99%
“…It leverages the implantation and epitaxial technique developed for IEMOSFETs to protect both the trench bottom and the relatively low-doped p-type epitaxial channel layer with the wet oxide, thereby providing high mobility. 22,30)…”
Section: Introductionmentioning
confidence: 99%
“…3) Many studies have recently demonstrated that trench MOSFETs have a relatively small specific on-resistance (R on A). [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] However, the reported field-effect channel mobility values of trench MOSFETs are in the range of 5-50 cm 2 V −1 s −1 , which is smaller than those of lateraltype MOSFETs using the same crystal phase (m-face or aface) for a channel. 3) In addition, since the trench sidewall that is the channel region of MOSFETs is difficult to evaluate, the mechanism that limits the channel mobility in trench MOSFETs is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…5) In fact, many reports have demonstrated several types of trench MOSFETs with relatively small specific-on-resistance (R on A) values. 3,[6][7][8][9][10][11][12][13][14][15][16][17] However, the use of trench MOSFETs still has challenges. One of the challenges is a channel mobility lower than that expected from lateral MOSFETs.…”
Section: Introductionmentioning
confidence: 99%